ANALISA ECONOMIC BASE TERHADAP PERTUMBUHAN EKONOMI DAERAH TINGKAT II WONOGIRI : MENGHADAPIIMPLEMENTASI UU NO. 22/1999 DAN UU NO. 5/1999 - Suyatno, Suyatno; Suyatno, Suyatno (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
This research aims at determining the sectors, which have regional superiority in Wonogiri, as the consequence of the implementation of Regulation 22/1999 and 25/1999. Furthermore, it also finds out deÂterminant factors, which cause positioning, and repositioning these sectors.LQ (Location Quotion) and DLQ (Dynamic Location Quotion) are used to determine superior sectors, and to identify determinant factors causing positioning and repositioning superior sectors, SSA (Shift Share Analysis) is used on this research.The result of this research indicates that statically, superior sectors in Wonogiri are: Agriculture; transport and communication ; Services; and Financial, ownership and business services. The sectors which are hoped to become superior in the next time are: Financial, ownership and business services; Agriculture; and Services. Positioning and repositioning superior sectors in Wonogiri are caused by Location superiority.